Pelatihan Deteksi Dini Anak Berkebutuhan Khusus Pada Guru Sekolah Dasar (SD) - Deden Mulyadi (Jurnal Studia Insania, 2022)
The increasing number of special needs children and the lack of SLB (Special Schools), so that the government makes an inclusive school program. That’s important for teachers with inclusion programs to have knowledge about the early detection of children with special needs. Based on the description above, the researchers are interested in designing a training program to increase knowledge about the early detection of children with special needs (ABK). Researchers focus on the early detection of children with special needs, namely children with autism, ADHD (attention Deficit and Hyperactivity Disorder), slow learners, and gifted. The formulation of the problem from this research is "can the early detection training of children with special needs for teachers improve teacher knowledge in early detection of children with special needs?". This study used a pre-experimental design, namely a single-group one-group pre-test-post-test design. The subjects in this study were teachers of SDIT Miftahul Ulum Depok, amounting to 15 people. The result of the research is that the training has succeeded in increasing participants' knowledge about the early detection of children with special needs.